(untitled) (Al-Qamar, 2019)
This study explores the various complex aspects of social justice and equality within the distinct societal context of Pakistan, with a focus on incorporating an Islamic perspective. This study examines how fundamental Islamic principles manifest inside the framework of Pakistani society, exerting an impact on social frameworks, policies, and day-to-day engagements. Also, it looks at historical examples within Islamic organizations that exemplify the manifestation of social justice and equality in government and social welfare. The strategies employed by Pakistan to address social difficulties through legal reforms, economic policies, and public awareness while maintaining a strong connection to its Islamic past are also explored. The primary areas of emphasis encompass the advancement of gender parity within the confines of delineated societal functions, the equitable allocation of resources via mechanisms like zakat, and the safeguarding of the rights of marginalized groups. Moreover, the study investigates methods for augmenting interfaith concordance and fortifying the legal structure to protect social justice and parity.